Serum 25 hydroxyvitamin D was positively associated with hemoglobin and other anemia parameters in children: a cross-sectional study. - Dong, Hongli; Xu, Xiaojing; Gao, Liang; Ni, Yufei (Nutrition & Metabolism, 2025)
Background: Previous in vitro studies indicated that 25 hydroxyvitamin D [25(OH)D] might contribute to the modulation of anemia parameters while epidemiological evidences were scarce in children. We explored the associations of 25(OH)D with hemoglobin (Hb) and other anemia parameters (mean corpuscular volume [MCV], mean corpuscular hemoglobin concentration [MCHC], and serum ferritin [SF]) in children. Methods: A cross-sectional study involving 10,227children (mean age 14.6 months) in Nantong, China, was carried out. Serum 25(OH)D, MCV, MCHC, and SF concentrations were measured. Results: After adjustment for the potential covariates, serum 25(OH)D was positively associated with anemia parameters (quartile [Q] 4 vs. Q1: 127.304 vs. 78.982 g/L for Hb; 83.957 vs. 66.264 fL for MCV; 334.551 vs. 208.368 g/L for MCHC; 34.277 vs. 32.807 ng/mL for SF). Similar results were shown in the stratified analyses by gender. Consistently, a higher 25(OH)D was found to be related with a lower risk of anemia (ORQ4 vs. Q1: 0.06, 95% CIQ4 vs. Q1: 0.05, 0.07) in multi-variable analysis among total populations. Additionally, the "25(OH)D–anemia parameters (Hb, MCV, and MCHC)" and "25(OH)D–anemia" associations were mediated by hsCRP. Conclusions: In general, our findings provided further support for the anti-anemia effects of 25(OH)D in Chinese children. Further research is warranted to replicate these results in different populations and in experimental settings.